Environmental impact of toxic heavy metal pollutants: A comprehensive study on phytoremediation mechanism and strategies - Yagyavalkya Sharma; Mamta Arya; Naina Srivastava; Bhavtosh Sharma; Mouli Nahar; Anjali Patil; Bhagyashree Debbarma (Environment Conservation Journal)
Heavy metals are becoming a serious threat to the sustainability of the environment. Therefore, their removal through various living organisms is necessary for a clean environment. This study aims to evaluate the mechanisms and effectiveness of  phytoremediation for metal treatment. The balance of the environment and human health is mainly impacted by the toxic contamination of heavy metals in soil, water, and the atmosphere. These toxic heavy metals can severely impact the environment and health of living organisms; therefore, their treatment becomes a necessity. In comparison to various expensive physical and chemical treatment strategies,  biological remediation can be considered environmentally sustainable and economically viable. Plants may be used to clean up the environment and prevent toxic contamination due to their unique metal resistance strategies. One of the most attractive and popular ways to use living organisms to break down dangerous heavy metal contaminants or to collect and stabilize them is through the use of plant-based technologies, which may be used as filters. This study examines various mechanisms (such as phytoextraction,  phytostabilization, and phytovolatilization) of plants for the mitigation of toxic metallic substances from the environment. During phytoremediation, various strategies such as complex enzyme systems (modify/biotransform heavy metals), root exudates (enhance the solubilization and root uptake of heavy metals), and metal-binding proteins (promote metal sequestration) help in metal accumulation and reduction from the environment. Furthermore, this review proves the significance of a plant-based bioremediation approach for the restoration of the environment through an effective and sustainable method.